Handbook of communication skills - Hargie,Owen (Routledge, 2006)
This new edition provides a comprehensive analysis of research, theory and practice in the key skill areas of communication. It examines in detail the core principle that interpersonal communication can be conceptualised as a form of skilled activity and presents a comprehensive transactional model of skilled communication.